Structure-specific DNA endonuclease Mus81/Eme1 generates DNA damage caused by Chk1 inactivation. - Josep V Forment; Melanie Blasius; Ilaria Guerini; Stephen P Jackson (PLoS ONE)
The DNA-damage checkpoint kinase Chk1 is essential in higher eukaryotes due to its role in maintaining genome stability in proliferating cells. CHK1 gene deletion is embryonically lethal, and Chk1 inhibition in replicating cells causes cell-cycle defects that eventually lead to perturbed replication and replication-fork collapse, thus generating endogenous DNA damage. What is the cause of replication-fork collapse when Chk1 is inactivated, however, remains poorly understood. Here, we show that generation of DNA double-strand breaks at replication forks when Chk1 activity is compromised relies on the DNA endonuclease complex Mus81/Eme1. Importantly, we show that Mus81/Eme1-dependent DNA damage--rather than a global increase in replication-fork stalling--is the cause of incomplete replication in Chk1-deficient cells. Consequently, Mus81/Eme1 depletion alleviates the S-phase progression defects associated with Chk1 deficiency, thereby increasing cell survival. Chk1-mediated protection of replication forks from Mus81/Eme1 even under otherwise unchallenged conditions is therefore vital to prevent uncontrolled fork collapse and ensure proper S-phase progression in human cells.